Identification of grain size and mineral distributions in the surface sediments of Red river estuaries in Vietnam - Bui Van Vuong; Nguyen Dac Ve; Nguyen Thi Mai Luu; Hoang Thi Chien; Nguyen Ngoc Nam; Lai Thi Bich Thuy; Nguyen Van Anh; Tran Duc Thanh; Dang Hoai Nhon (Vietnam Journal of Science, Technology and Engineering)
The mineral composition and grain size of surface sediments from the estuaries of the Red river system were analysed to assess the dynamics and origin of the sediments. Five types of sediments are distributed in river mouths: coarse silt, very fine sand, very coarse silt, fine sand, and medium silt. The mineral contents in the sediment were as follows: quartz 46.0%, illite 18.3%, kaolinite 11.8%, chlorite 6.4%, feldspar 6.0%, goethite 4.4%, calcite 1.9%, gibbsite 1.7%, and amphibole 1.4%. There were two sediment groups: Group 1 was weakly dynamic, and Group 2 was strongly dynamic. The minerals in the sediments were mainly continental, characterised by illite, kaolinite, chlorite, quartz, feldspar, and amphibole, with other sources, including precipitation and weathering, being limited.